Evolutionary origins and genetic variation of the Seychelles treefrog, Tachycnemis seychellensis (Duméril and Bibron, 1841) (Amphibia: Anura: Hyperoliidae) - Maddock, Simon T. (Academic Press, 2014)
The hyperoliid frog Tachycnemis seychellensis, the only species of its genus, is endemic to the four largest granitic islands of the Seychelles archipelago and is reliant on freshwater bodies for reproduction. Its presence in the Seychelles is thought to be the product of a transoceanic dispersal, diverging from the genus Heterixalus, its closest living relative (currently endemic to Madagascar), between approximately 10–35 Ma. A previous study documented substantial intraspecific morphological variation among island populations and also among populations within the largest island (Mahé). To assess intraspecific genetic variation and to infer the closest living relative(s) of T. seychellensis, DNA sequence data were generated for three mitochondrial and four nuclear markers. These data support a sister-group relationship between T. seychellensis and Heterixalus, with the divergence between the two occurring between approximately 11–19 Ma based on cytb p-distances. Low levels of genetic variation were found among major mitochondrial haplotype clades of T. seychellensis (maximum 0.7% p-distance concatenated mtDNA), and samples from each of the islands (except La Digue) comprised multiple mitochondrial haplotype clades. Two nuclear genes (rag1 and tyr) showed no variation, and the other two (rho and pomc) lacked any notable geographic structuring, counter to patterns observed within presumably more vagile Seychelles taxa such as lizards. The low levels of genetic variation and phylogeographic structure support an interpretation that there is a single but morphologically highly variable species of Seychelles treefrog. The contrasting genetic and morphological intraspecific variation may be attributable to relatively recent admixture during low sea-level stands, ecophenotypic plasticity, local adaptation to different environmental conditions, and/or current and previously small population sizes. Low genetic phylogeographic structure but substantial morphological variation is unusual within anurans.